PELATIHAN PEMBUATAN AROMATERAPI LAVENDER & GRASS OIL (ALTERNATIF PENCEGAH DBD) DAN LEMON & GREENTEA (KARMINATIF) - Turahman, Taufik; Rahayu, Mamik Ponco; Fadma Sari, Ghani Nurfiana; Rejeki, Endang Sri; Harmastuti, Nuraini; Supriyadi, Supriyadi (Politeknik Indonusa Surakarta, 2023)
The Lavender and Grass oil Aromatherapy Making Training is a Community Service project to disseminate relevant knowledge and technology that is easy to use. In addition, it provides value by improving skills and motivate to establish a home industry in the pursuit of a small business. A USB Pharmacy lecturer conducted this program for people of the Genengan community, located at RT 08 RW 12, Mojosongo Village, Jebres Sub-district, Surakarta City. Oils from Lemongrass and Lavender Herbs are used in aromatherapy making training. These organic components have not yet been utilized by community members or locals to produce aromatherapy that is beneficial to their health. Typically, pharmacies charge relatively high costs for products that include aromatherapy. It is envisaged that the Geneng community's training in aromatherapy production will boost the village's added value. Making products for aromatherapy using lavender and lemongrass is one of the projects that has the potential to be used as a home industry activity.